Measurement and simulation of magnetic field of a 132kV air-insulated substation in Malaysia - Said I.; Farag A.S.; Hussain H.; Rahman N.A. (2023)
This paper presents magnetic field measurement results of a 132kV transmission substation in Malaysia. Magnetic fields produced by sources such as transformers, busbars, incoming and outgoing transmission lines and cables were thoroughly studied. Software model of the substation was constructed and verified. Simulation studies were conducted for various change in substation parameters such as conductor spacing and bus height and the resulting magnetic fields were compared against existing ones.